Two new critically endangered species of Vellozia (Velloziaceae) from the Campos Rupestres of Espinhaço Range, Brazil - Magri, R.a.; Cabral, A.; Prado, J.; Lopes, J.c. (Phytotaxa, 2024)
Two new narrowly distributed species of Vellozia (Velloziaceae) are described, illustrated, and a preliminary status of conservation was assessed, Vellozia flavida Mello-Silva ex Magri and V. formosa Mello-Silva ex Magri. Both species occur in the municipality of Monte Azul, Minas Gerais State, Brazil, in the Campos Rupestres vegetation. Vellozia flavida is closely related to V. luteola and both are easily recognized by having yellow perianth, an uncommon character in the genus. Vellozia flavida however is distinguished by the high number of stamens (22) and the presence of capitate hypanthial emergences, whereas V. luteola has 15 stamens and subulate hypanthial emergences. Vellozia formosa is morphologically related to V. nanuzae, showing similar habits, however, it is distinguished by the leaf blades covered with long emergences on both surfaces vs. glabrous in V. nanuzae. Due to the narrow distribution of V. flavida and V. formosa and threats to their habitat such as mining and livestock industries, they were considered as critically endangered (CR) according to IUCN criteria.